Molecular recognition and spectral tuning of organic dyes in water by amide naphthotubes. Issue 67 (1st August 2022) - Chen, Zhao; Quan, Mao; Dong, Yi-Wei; Li, Ming-Shuang; Wang, Song-Meng; Zhao, Lei-Min; Yang, Liu-Pan; Wu, Jishan; Jiang, Wei
Abstract : Molecular recognition and spectral tuning of organic dyes were achieved in water by amide naphthotubes. The association affinity is up to 4.5 × 10 7 M −1, and great fluorescence enhancement was observed for styryl derivatives. Abstract : Molecular recognition and spectral tuning of 13 organic dyes were achieved in water by amide naphthotubes. The association affinity to a styryl derivative is up to 4.5 × 10 7 M −1, which is the highest among all the known hosts. In addition, great fluorescence enhancement was observed for styryl derivatives. This would lay a basis for the potential analysis application.